2005
DOI: 10.1002/eat.20186
|View full text |Cite
|
Sign up to set email alerts
|

A naturalistic evaluation of the relation between dietary restraint, the urge to binge, and actual binge eating: A clarification

Abstract: Results suggest that dietary restraint may contribute to binge cravings, but may not be a direct antecedent to binge episodes. Such findings are consistent with restraint theory, which suggests that dietary restraint potentiates binging, but does not necessarily trigger its occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…An alternative explanation refers to this study's operationalization of mood: The present study focused on overall negative mood proposed to be involved in the maintenance of binge eating, 2-5 but it cannot be ruled out that specific negative or positive emotional qualities would show a different course as suggested by retrospective data on anxiety reduction, 7 hedonics of binge eating, 9 and by EMA data on pleasantness. 18 Further research using concurrent assessment of specific qualities of mood over the course of binge eating would be desirable, simultaneously considering other putative maintaining factors and association with them, for example, restraint or low self-concept, 3,14,15,39 further clarifying the reinforcing potential of binge eating.…”
Section: Resultsmentioning
confidence: 98%
“…An alternative explanation refers to this study's operationalization of mood: The present study focused on overall negative mood proposed to be involved in the maintenance of binge eating, 2-5 but it cannot be ruled out that specific negative or positive emotional qualities would show a different course as suggested by retrospective data on anxiety reduction, 7 hedonics of binge eating, 9 and by EMA data on pleasantness. 18 Further research using concurrent assessment of specific qualities of mood over the course of binge eating would be desirable, simultaneously considering other putative maintaining factors and association with them, for example, restraint or low self-concept, 3,14,15,39 further clarifying the reinforcing potential of binge eating.…”
Section: Resultsmentioning
confidence: 98%
“…For example, as long ago as 1985, Schlundt et al found that extreme hunger ratings were strongly associated with binge craving in a bulimic sample (Schlundt et al, 1985). More recently, Engelberg et al (2005) noted that dietary restraint contributes to binge cravings rather than being a direct antecedent of bingeing. Given these findings, some authors have concluded that engaging in dietary restraint may lead to an increase in the reinforcing quality of foods for the individual (Stickney et al, 1999).…”
Section: Factors Contributing To Binge Eatingmentioning
confidence: 96%
“…18,101,113,114,117,118 Others note that dietary restraint contributes to binge cravings rather than being a direct antecedent. 119 Differences in dieting do not appear to be a factor preceding a binge episode across the diagnostic eating disorder categories. 101 Distorted cognitions related to perceived pressure to be thin and body dissatisfaction, 7,118,120 negative thoughts about oneself, 103 food cravings, 98,99 thoughts of food and planning binge episodes have all been reported to occur before a binge episode.…”
Section: Other Attributes Of a Bingementioning
confidence: 97%